Ectopic expression of CsMADS24, an AGAMOUS ortholog from cucumber, causes homeotic conversion of sepals into carpels in transgenic Arabidopsis plants - Zhou, Yong; Hu, Lifang; Ge, Lingli; Li, Guanghua; He, Peng; Jiang, Lunwei; Liu, Shiqiang (Archives of Biological Sciences, 2019)
The floral homeotic C-function MADS gene AGAMOUS (AG) in Arabidopsis plays crucial roles in specifying stamen and carpel identities as well as determining floral meristem. However, there have been only a few studies of floral homeotic C-function genes in cucumber thus far. In the present study, CsMADS24, a putative AG ortholog from cucumber, was isolated and characterized. Sequence analysis and protein sequence alignment revealed that the deduced CsMADS24 protein contained the typical MIKC structure and the N-terminal extension, as well as two highly conserved AG motifs (I and II). Phylogenetic analysis showed that CsMADS24 fell into the clade of core eudicots, while being distant from the AG orthologs of basal eudicots, monocots and gymnosperms. Expression analysis by RT-PCR showed that CsMADS24 was exclusively expressed in female flower buds. In situ hybridization revealed that CsMADS24 expression was only detected in the carpels. Functional analyses indicated that the sepals were partly converted into carpelloid-like structures in 35S::35S::CsMADS24 transgenic plants. In addition, earlier flowering and delayed floral organ abscission during the development of siliques were also observed in transgenic Arabidopsis. Our findings demonstrate that the AG ortholog plays an exclusive role in carpel specification of cucumber, providing a basis for revealing the mechanisms of reproductive development in cucumber. https://doi.org/10.2298/ABS180528037Z Received: May 28, 2018; Revised: July 23, 2018; Accepted: August 22, 2018; Published online: August 29, 2018 How to cite this article: Zhou Y, Hu L, Ge L, Li G, He P, Jiang L, Liu S. Ectopic expression of CsMADS24, an AGAMOUS ortholog from cucumber, causes homeotic conversion of sepals into carpels in transgenic Arabidopsis plants. Arch Biol Sci. 2019;71(1):13-20.